Gliomatosis Cerebri (GC), Presentation, Management & Prognostic Overview - Raad Ahmed Hussein (Journal of Global Pharma Technology, 2016)
Gliomatosis cerebri (GC) is a rare, infiltrating glioma of brain & spinal cord. It is affects children, adult & elder age groups. Objective: To have an overview on the clinical presentation, management, prognosis & survival period of patients with GC. Material & methods: We retrospectively studied the clinical presentation & management and prognosis in 14 patients of gliomatosis cerebri between 2013 and 2016. The presentation is that of raised ICP, focal neurodeficit & epilepsy.  Results: All patients treated with radiotherapy, followed in few cases by chemotherapy. The survival time was not more than 2 years in all cases. The diagnosis is based on radiological MRI studies & histopathology.  Treatment: Surgical treatment is not usual option due to wide spread neuraxis involvement. Radiation therapy & chemotherapy may give some survival benefit. The outcome of the disease & the prognosis is poor & the survival period not exceeds 24 months with the best combined chemotherapy & radiotherapy.Keywords: Multiple malignant glioma. Gliomatosis  cerebri.